Implementation of the Scientific Foundation of Vocational Education in the Implementation of Vocational Education at the Lembaga Kursus Dan Pelatihan (LKP) Zere - Amin - Amin, Elvira Dwi Rahayu; Triono, Selamat; Sarwa, Sarwa (Jurnal Riset Ilmu Pendidikan, 2025)
Research on the implementation of the scientific basis for vocational education in the implementation of vocational education at the course and training institution (LKP) Zere – Amin is based on the general view that formal and non-formal educational institutions are capable of producing individuals who are independent and have the expertise and skills to live life, especially in this world Work. The aim of this research is to find out and describe vocational education at LKP Zere Amin. The type of research used is field research, with a qualitative descriptive approach that has been obtained from the field and related literature. To obtain data through observation and interviews. The results of this research show that the management of vocational education at LKP Zere Amin, through skills training activities in the field of Fashion Design, organizes a work skills program, namely the vocational education implementation model uses a cooperative/dual system model. This model is also called the government-controlled market model, this model is called a dual system where the learning system is implemented in two locations, namely at LKP and at work partners (DU/DI) both of which help each other in creating capabilities. reliable graduate work. Carrying out good partnership program planning between LKP - Zere Amin and DU/DI with the result that DU/DI is able to contribute to LKP. The form of collaboration carried out in this case is curriculum preparation, DU/DI visits, guest teachers, learning, evaluations carried out at the end of learning, and job recruitment for graduates.